A model to predict difficult airway alerts after videolaryngoscopy in adults with anticipated difficult airways – the VIDIAC score. (25th August 2022) - Kohse, E. K.; Siebert, H. K.; Sasu, P. B.; Loock, K.; Dohrmann, T.; Breitfeld, P.; Barclay‐Steuart, A.; Stark, M.; Sehner, S.; Zöllner, C.; Petzoldt, M.
Summary: A model to classify the difficulty of videolaryngoscopic tracheal intubation has yet to be established. The videolaryngoscopic intubation and difficult airway classification (VIDIAC) study aimed to develop one based on variables associated with difficult videolaryngoscopic tracheal intubation. We studied 374 videolaryngoscopic tracheal intubations in 320 adults scheduled for ear, nose and throat or oral and maxillofacial surgery, for whom airway management was expected to be difficult. The primary outcome was whether an anaesthetist issued a 'difficult airway alert' after videolaryngoscopy. An alert was issued after 183 (49%) intubations. Random forest and lasso regression analysis selected six intubation‐related variables associated with issuing an alert: impaired epiglottic movement; increased lifting force; direct epiglottic lifting; vocal cords clearly visible; vocal cords not visible; and enlarged arytenoids. Internal validation was performed by a 10‐fold cross‐validation, repeated 20 times. The mean (SD or 95%CI) area under the receiver operating characteristic curve was 0.92 (0.05) for the cross validated coefficient model and 0.92 (0.89–0.95) for a simplified unitary score (VIDIAC score with component values of −1 or 1 only). The calibration belt for the coefficient model was consistent with observed alert probabilities, from 0% to 100%, while the unitary VIDIAC score overestimated probabilities < 20% and underestimated probabilities > 70%. Discrimination of the VIDIAC score for patients more or less likely to be issued an alert was better than discrimination by the Cormack–Lehane classification, with mean (95%CI) areas under the receiver operating characteristic curve of 0.92 (0.89–0.95) vs. 0.75 (0.70–0.80), respectively, p < 0.001. Our model and score can be used to calculate the probabilities of difficult airway alerts after videolaryngoscopy.